Numerical simulation of lean premixed combustion characteristics and emissions of natural gas-ammonia dual-fuel marine engine with the pre-chamber ignition system. (1st July 2023) - Wu, Xuefei; Feng, Yongming; Gao, Yuanxin; Xia, Chong; Zhu, Yuanqing; Shreka, Majed; Ming, Pingjian
Highlights: A CH4 /NH3 mechanism is developed and experimentally verified. Ammonia pyrolysis in the pre-combustion chamber promotes the flame propagation. NOx emissions decreased with the further increase of ammonia (when NH3  > 50%). N2 O emissions partially offset the CO2 emission reduction effect. Ammonia is a suitable candidate fuel applied for natural gas marine engine. Abstract: As an efficient hydrogen carrier, ammonia (NH3 ) has great potential to realize the target of carbon neutralization. In this paper, a natural gas-ammonia dual-fuel engine model has been established to evaluate the feasibility of ammonia application in a high-pressure medium-speed four-stroke natural gas marine engine. In order to achieve the efficient and clean combustion of ammonia, a method combining the pre-chamber ignition system with lean-burn combustion technology was proposed. In addition, a CH4 /NH3 combustion mechanism with reasonable accuracy was developed to simulate the combustion process of the engine. Moreover, the effect of using various ammonia concentration in the fuel on jet flame formation, thermal efficiency, unburned ammonia, and NOx and N2 O emissions were compared. The results showed that the pyrolysis of ammonia mixtures in the pre-combustion chamber promoted the formation of jet flame, which had a "chain effect" on the turbulent kinetic energy in the main combustion chamber and further enhanced the flame propagation in lean conditions. In addition, NOx emission showed a decreasing function of the split ratio of ammonia, which was caused by the NO reduction by unburned NH3 . However, the low-temperature generation characteristics of N2 O emissions led to the opposite trend. Furthermore, the application of ammonia increased N2 O emissions by 0.18–0.49 g/kWh, which is about 0.06%–0.1% of nitrogen in ammonia fuel, resulting in a partial offset of CO2 emission reduction effect.